Al-Yusru-Based Community Service: Implementation of Vital Signs Monitoring System (AL-YUSVID) at PPTQ Daarul Quran As-Syafaah, Kedung Ringin, East Lampung - Heni Sumarti; Irman Said Prastyo (Community Research and Application Journal (CRAJ), 2025)
Routine monitoring of vital signs is an important aspect in disease prevention and early detection efforts. Conventional methods are often time-consuming and inefficient, especially in community health services. This community service activity was conducted by the Physics Department Team of Universitas Islam Negeri Walisongo Semarang in collaboration with PPTQ Daarul Quran As-Syafaah to test the implementation of the AL-YUSVID (Al-Yusru Integrated Vital Signs Detection) prototype in monitoring vital signs in the Kedung Ringin community, East Lampung. The AL-YUSVID prototype, developed based on the principle of al-Yusru (ease and sustainability), was tested to measure oxygen saturation (SpO2), heart rate, and body temperature in 25 participants. This activity increased community awareness about the importance of routine health monitoring and demonstrated the potential of non-invasive website-based technology in community health services.